Optical Coherence Tomography Angiography Findings in Primary Open- Angle and Pseudoexfoliation Glaucoma - Emrah Düzova; Gülizar Demirok; Güner Üney; Ahmet Kaderli; Mehmet Yakın; Selma Özbek-Uzman; Ümit Ekşioğlu (Türk Oftalmoloji Dergisi, 2022)

(untitled)
Objectives:To compare the optical disc and macular vascular density values of patients with glaucoma and healthy individuals by using optical coherence tomography angiography and evaluate the relationship between structural and functional test results and vascular density.Materials and Methods:The study included 128 eyes in total: 31 with pseudoexfoliation glaucoma (PEG), 55 with primary open-angle glaucoma (POAG) and similar visual field defects, and 42 healthy eyes. Whole image peripapillary vessel density (wpVD), intradisc vessel density (idVD), peripapillary vessel density (pVD), whole image macular vessel density (wmVD), and parafoveal vessel density (pfVD) values were compared between the groups. Correlations between visual field findings, retinal nerve fiber layer (RNFL) and optic nerve head measurements and peripapillary and macular vascular density were analyzed.Results:In the PEG and POAG groups, wpVD, idVD, wmVD, and pfVD values were significantly lower in than the control group. In the PEG group, wpVD was found to be significantly lower than the POAG group (p<0.001). There was no significant difference between the PEG and POAG groups in wmVD and pfVD except for nasal pfVD. There were strong positive correlations between RNFL thickness and pVD in the glaucoma groups (p<0.001). Significant correlations were found between visual field mean deviation and pattern standard deviation values and peripapillary and macular vessel density values in the glaucoma groups.Conclusion:Vascular density values were lower in glaucoma patients compared to normal individuals, and there is a strong correlation between structural and functional tests and vessel density values. The lower vascular density in the PEG group compared to the POAG group indicates that vascular damage may be more common in PEG patients.